MODEL MISI GEREJA MENGHADAPI AJARAN SESAT DALAM SURAT PAULUS KEPADA TIMOTIUS SEBAGAI PEGANGAN GEREJA BETHEL INDONESIA MOJOPAHIT JEMBER - Djohan Rusli (STAK Reformed Remnant Internasional, 2023)
Christians need to understand the model of church's mission in dealing with heresy as a handle on life today. While the advancement of information and technology is very rapid, especially in the field of social media, congregation's very minimum knowledge on the word of God becomes a serious threat to church with a variety of teaching impressions that cannot be accounted for the truth; irrelevant with the Gospel of Jesus Christ. The results of research and theoretical studies revealed that the church mission model following the mission of Christ is needed, namely: evangelism model, discipleship model, church development model, and teaching model in the face of heresy; where all these models focus on the Gospel of Jesus Christ. The research was conducted using qualitative methods to obtain accurate data, supported by theological approaches, literature, and case studies to produce descriptive data. This article aims to find a model of the church's mission in dealing with heresies as the church's grip.